The effect of premature polymerization from ambient light on the working time and fracture toughness of visible light curing composites, SY 2005-2006 - Chiu, Joanna Joy N.
This study aimed to determine the effect of premature polymerization upon ambient light exposure on the working times and fracture toughness of different composite materials. The study was divided into two phases: 1) the determination of the working time of composites under ambient light 2) the determination of fracture toughness values of composites with different natures of polymerozation. Four brands of composite materials (two microhybrids and two nanohybrids were used in this study. For the first phase, a clinical simulation was performed under a fixed distance from a dental operatory light. The composites' optimal and maximal working times were recorded during the simulation. Results from the first phase were used for the second phase, wherein the composites were manipulated while exposed to a dental operatory light until their mean working times in a mould, and then light cured for 40 seconds. The samples were tested for fracture toughness using an Instron Universal Testing Machine. Results of the first phase showed no significant difference in the optimal working times of the composites. However, there was a significant difference in the maximal working time of Composite E compared with the other brands. Results of the second phase showed no significant difference in the fracture toughness within and among the 4 brands of composites having different natures of polymerization. Based from the results, fractures toughness of the composites tested is not affected significantly by premature polymerization from ambient light. However, their working times have shown to be limited by it.